Effects of Meditation on the T-lymphocytes, B-lymphocytes and Natural Killer Cells Production - Yaovaluk Nuamtanung; Surapol Vorapongpiboon; Amara Thongpan; Supaporn Boonyaprasit (Agriculture and Natural Resources, 2005)
The effects of meditation practice on the production of T-lymphocytes, B-lymphocytes and natural killer cells (NK) were evaluated in two groups of volunteers. Group I consisted of experienced meditators of more than two years while group II was inexperienced new comers. The selected healthy volunteers have to practice meditation one hour daily for a period of four months. Venipuncture was done at the beginning (month 0) and at the end of the 4-month meditation. Fluorochrome conjugated monoclonal antibody to CD45, CD3, CD5, CD4, CD8, CD19 and CD(16+56) were incubated with peripheral blood lymphocytes and the number of positively labeled lymphocytes were determined by flow cytometer. The statistical analysis showed that CD3+ lymphocytes were significantly increased in both groups of volunteer after meditation practice for four months. In group I, the numbers of CD3+, CD8+ and CD(16+56)+ lymphocytes of experienced meditators were significantly increased (P<0.05, P<0.01 and P<0.01, respectively). For the inexperienced group, CD45+ lymphocytes were significantly increased (P < 0.05) as well as CD3+, CD5+ and CD8+ lymphocytes (P < 0.01). No alteration of CD19+lymphocytes and no correlation between CD4+ and CD(16+56)+ lymphocytes were observed in both groups. The results presented herein indicated that meditation practice might aid in improvement of the immune system, especially the production of T-lymphocytes and natural killer cells.